2014
DOI: 10.1021/bc5002856
|View full text |Cite
|
Sign up to set email alerts
|

Development of BODIPY FL Vindoline as a Novel and High-Affinity Pregnane X Receptor Fluorescent Probe

Abstract: The pregnane X receptor (PXR) regulates the metabolism and excretion of xenobiotics and endobiotics by regulating the expression of drug-metabolizing enzymes and transporters. The unique structure of PXR allows it to bind many drugs and drug leads, possibly causing undesired drug–drug interactions. Therefore, it is crucial to evaluate whether chemicals or drugs bind to PXR. Fluorescence-based assays are preferred because of their sensitivity and nonradioactive nature. On the basis of our previously characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 34 publications
3
52
0
Order By: Relevance
“…The normalized results for each chemical were fitted into a one-site competitive binding equation with GraphPad Prism to derive the IC 50 values. In the test, the positive control T0901317 had an IC 50 value of 95.9 ± 7.0 nM, which is consistent with the value of 101.6 nM previously recorded under similar assay conditions49.…”
Section: Methodssupporting
confidence: 89%
“…The normalized results for each chemical were fitted into a one-site competitive binding equation with GraphPad Prism to derive the IC 50 values. In the test, the positive control T0901317 had an IC 50 value of 95.9 ± 7.0 nM, which is consistent with the value of 101.6 nM previously recorded under similar assay conditions49.…”
Section: Methodssupporting
confidence: 89%
“…We performed statistical calculations by using one-way analysis of variance with Tukey’s multiple-comparison test or a paired t -test when comparing two groups. Sample sizes were chosen according to previous studies that showed statistical significance 27 , 35 , 47 , which also contained information on assay validation and determination of Z’ factor (a measure of statistical effect size) 47 . No data were excluded from the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous NR LBD-based biosensors have been developed, principally in the context of drug development [ 166 , 190 ]. Among the established xenobiotic receptors, the human PXR LBD has been successfully used as the sensor element in a number of differing biosensor formats [ 111 , 191 , 192 ]. Such biosensors have confirmed previously known human PXR ligands such as hyperforin, clotrimazole, ginkgolide A, SR12813, and 5b-pregnane-3,20-dione [ 111 , 112 , 191 ].…”
Section: Development Of High-throughput Bioassays Based On Marine mentioning
confidence: 99%
“…Among the established xenobiotic receptors, the human PXR LBD has been successfully used as the sensor element in a number of differing biosensor formats [ 111 , 191 , 192 ]. Such biosensors have confirmed previously known human PXR ligands such as hyperforin, clotrimazole, ginkgolide A, SR12813, and 5b-pregnane-3,20-dione [ 111 , 112 , 191 ]. The successful development of human PXR LBD-based biosensors supports the theoretical feasibility of using marine invertebrate XANR LBDs in biosensor formats to screen for marine bioactive compounds.…”
Section: Development Of High-throughput Bioassays Based On Marine mentioning
confidence: 99%